2018
DOI: 10.1016/j.tplants.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing and Distributed Computation in Plant Organs

Abstract: The molecular networks plant cells evolved to tune their development in response to the environment are becoming increasingly well understood. Much less is known about how these programs function in the multicellular context of organs and the impact this spatial embedding has on emergent decision-making. Here I address these questions and investigate whether the computational control principles identified in engineered information processing systems also apply to plant development. Examples of distributed comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 73 publications
1
38
0
Order By: Relevance
“…In light of the central role of cell-to-cell communication in SAM function ( Jönsson et al., 2006 , Smith et al., 2006 , de Reuille et al., 2006 , Heisler et al., 2005 , Stoma et al., 2008 , Bayer et al., 2009 ), these structural networks represent the “roadmaps” upon which molecular processes unfold over these multicellular templates ( Jackson et al., 2017a ). Edges provide the routes of possible “information flow” across the structural template of cells in the SAM ( Bassel, 2018 ) and not necessarily observed functional communication between adjacent cells.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the central role of cell-to-cell communication in SAM function ( Jönsson et al., 2006 , Smith et al., 2006 , de Reuille et al., 2006 , Heisler et al., 2005 , Stoma et al., 2008 , Bayer et al., 2009 ), these structural networks represent the “roadmaps” upon which molecular processes unfold over these multicellular templates ( Jackson et al., 2017a ). Edges provide the routes of possible “information flow” across the structural template of cells in the SAM ( Bassel, 2018 ) and not necessarily observed functional communication between adjacent cells.…”
Section: Resultsmentioning
confidence: 99%
“…Bose further suggested that all plants are sensitive explorers of their world, responding to it through a fundamental, pulsatile motif involving coupled oscillations in electric potential, turgor pressure, contractility, and growth (reviewed by [117]). Although several aspects of Darwin’s ‘root-brain’ hypothesis remain controversial, as recently discussed [118], it is widely accepted that plants perform sophisticated information processing and computation, which rely on learning and memory [119,120,121,122,123,124,125]. These features are common to plants and animals, and underlie their adaptation to the continuously changing environment [126,127].…”
Section: Discussionmentioning
confidence: 99%
“…Plant tissues are solid masses made of rigid, space-filling cells [43]. This severely constrains the design space in terms of network topologies that is available to tissue formation [38]. Isotropy and lattice-like organs (figure 2 b ) are frequently found in plants; this constitutes a limiting factor in how fast information can be transmitted through plant organs [70].…”
Section: Discussionmentioning
confidence: 99%
“…Organs in general, including those from plants, operate under similar conditions to distributed computing. They do not rely on a single CPU/cell to govern action, instead goal-oriented behaviour is broken down into smaller tasks and allocated into the many constituent cells [38] (figure 2 a,b ). A consensus such as determining organ size or timing for a developmental transition is then reconstructed from the small-scale cellular contributions by aggregation.…”
Section: Introductionmentioning
confidence: 99%